2010
DOI: 10.1007/s00253-010-2466-x
|View full text |Cite
|
Sign up to set email alerts
|

Mercury resistance and accumulation in Escherichia coli with cell surface expression of fish metallothionein

Abstract: Recombinant tilapia (Oreochromis mossambicus) fish metallothionein (MT) was used as a surface biosorbent for mercury removal in Escherichia coli. Fish MT conferred better resistance than did mouse or human MT. When tilapia MT (tMT) was fused with an outer-membrane protein, outer membrane protein C (OmpC), the membrane-targeted fusion protein, OmpC-tMT, gave enhanced resistance compared with cytoplasmic tMT expressed in the same host cell. The cytoplasmically expressed tMT showed high mercury adsorption (4.3 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…This could also be explained by its osmoregulation ability. Interestingly, the tolerances of MMT performed better than TMT in furfural (Figure 4a), Our previous studies [26], we found MT display different scavenging capacity between two kinds of radicals (ABTS ●+ and DPPH ● ). We suggested that MMT prefers to scavenge the type of ROS generated from furfural.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…This could also be explained by its osmoregulation ability. Interestingly, the tolerances of MMT performed better than TMT in furfural (Figure 4a), Our previous studies [26], we found MT display different scavenging capacity between two kinds of radicals (ABTS ●+ and DPPH ● ). We suggested that MMT prefers to scavenge the type of ROS generated from furfural.…”
Section: Resultssupporting
confidence: 63%
“…In this study, it was hypothesized that the increased alcohol tolerance in engineered E. coli strains was due to the ability of MTs, particularly the TMT strains, to possess higher scavenging efficiencies as previously reported [26]. Overall, both membrane-targeted MMT and TMT strains were found contributing to 3 times n- butanol (0.5% to 1.5%) and 1.25 times ethanol (4% to 5%) greater tolerances, respectively, than the control E. coli strains (pET30a).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Its adsorption efficiency was 7-fold higher than the control Top10/pBAT1, with 100% of Hg 2+ ranging from 0.1 to 100 nM adsorbed. This adsorption efficiency was higher than the genetically engineered bacteria E. coli strains overexpressed a single membrane component from a Bacillus mer operon (BMerP) and a tilapia metallothionein (tMT), which showed 27 and 25% increase in Hg 2+ adsorption efficiency [47,48]. Since no cysteine presented in the amino acid sequence, Gst Pm -4 may adsorb Hg 2+ via several charged surface functional groups like carboxyl, amino, carbonyl and hydroxyl that could interact with Hg 2+ through ion exchange and complex formation [42,49].…”
Section: Discussionmentioning
confidence: 95%
“…10 However, it was found that the addition of a Hg 2+ transport system, encoded by the merT and merP genes, were essential for mercury sequestration. An alternative strategy uses cell-surface displayed mercury-binding proteins, such as a metallothioneins, 11 phytochelatins, 12 or the MerR metal binding domain, 13 to create engineered cellular biosorbents. These examples of engineered bacterial circuits for sensing and absorption of mercury demonstrate the exciting potential of green biological strategies for mercury remediation of contaminated environments.…”
mentioning
confidence: 99%